Character Education Value Content in a Collection of Short Stories Compass 2018 Doa yang Terapung - Prarasto Miftahurrisqi; Suyitno; Sumarwati (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
Character education can be instilled in various ways. One of them is through literature. Literature itself is very diverse until now. Among young people, one of the works that have a lot of interest is short stories (short stories), because a short story contains interesting stories to read. In addition, the work also contains a message about positive things. This study aims to describe the value of character education in the collection of short stories Compass 2018 Doa Yang Terapung. Research is included in qualitative research. The method in this study uses descriptive qualitative. The data source in this study is a collection of short stories from Compass 2018 Doa Yang Terapung. Data collection in this study was carried out by reading and understanding short stories and recording data containing the value of character education in the 2018 Compass short story collection Doa Yang Terapung. Data analysis in this study uses the Miles and Huberman flow model, namely data reduction, data presentation, and concluding. The results of this study indicate the values of character education in the 2018 Kompas short story collection Doa Yang Terapung, among others a) the value of religious character education (the value of religious character praying to God, the value of religious character accepting destiny, the value of religious character believing & surrendering to God's destiny; b) the value of nationalist character education (the value of nationalist character, the spirit of heroism, the value of nationalist character). willing to sacrifice for his family, and c) the value of independent character education (character values of a good work ethic, professional character values, creative character values).